PRINCIPAL'S ASSERTIVENESS IN MAKING DECISIONS WITH HIGH COMMITMENT - Azi Rivaldi; R. Madhakomala (Ravine Publisher, 2024)
Assertiveness as a leader is a must, without clear assertiveness a leader will be easily influenced by others. As a good and firm leader, a school principal's assertiveness in making decisions is essential for upholding justice and discipline within the school organization. However, in this era of globalization, even though many advances in science and technology are developing very rapidly, human resources in Indonesia are still relatively low, especially in the field of educational institutions, namely in the decision-making process within school organizations. Therefore, the need for a firm leadership school in making decisions. This research method uses qualitative research methods with a literature approach. The data sources for this research come from relevant books and journals in line with the topic of discussion. The results of this research. A school principal, in leading an organization, must be able to have a firm nature both in terms of regulations and in making decisions through deliberation and must be able to uphold a commitment to decisions that have been made through deliberation.